Intensive care units: nursing staff’s attitudes towards euthanasia - Giakis, N; Polichronopoulou, E; Adali, E; Merkouris, Anastasios (My University, 2005)
Aim: The purpose of the present study is to investigate the attitude of Intensive Care Unit (ICU) nursing staff towards euthanasia of critically ill patients and the correlation of the findings with demographic and other factors. Material – Method: A self-completed questionnaire was distributed to the sample of the study which included 85 members of a general, an oncology and a pediatric hospital ICU nursing staff. Results: The results revealed that a 44.7% of the staff, is in favor of euthanasia but their knowledge is limited (5.9%), or very limited (32.9%), while the main source of information are the media and the magazines (52.9%). In the question that investigates will of participation, after the patient's demand and given law's permission, to stop or not even begin treatment in patients with end stage disease, 27.1% is opposite, 42.3% is in favor and 30.6% remains indecisive. 50.50% of the sample agrees to legislate late euthanasia under certain conditions, while the 22.4% of the sample remains indecisive. The most important factor in making the decision, was considered the incurable disease, while persistent demand of the family or psychiatric evaluation, were considered less important. Moreover, the staff of the ICU of the pediatric hospital was more positive, in participation in euthanasia under certain circumstances. Conclusion: The education and the information of the staff were considered of great importance in the sensitive issue of euthanasia, as well as a further exploration of the results of the present study.